DETERMINANTS OF ADHERENCE TO TAKING MEDICATION IN PULMONARY TUBERCULOSIS PATIENTS - Fitratul Harits; Nani Sari Murni; Lilis Suryani (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria that most often affects the lungs and even other organs. WHO stated that in 2021 there will be 10 million people infected with pulmonary Tb each year, and 1.5 million people die each year. Based on the results of the Basic Health Research conducted by the Research and Development Agency of the Ministry of Health of the Republic of Indonesia in 2018, there were 1,017,290 cases of pulmonary Tb in Indonesia. The effects of patient non-adherence in Tb treatment can increase the risk of morbidity, mortality and drug resistance both in patients and in the wider community. The purpose of this study was to analyze various factors associated with adherence to taking medication in patients with pulmonary Tb in the work area of the Tanjung Baru Health Center, Ogan Komering Ulu Regency in 2025. This study is a type of observational analytic research using a quantitative approach and cross-sectional design. The research was conducted in the work area of the Tanjung Baru Health Center, OKU Regency in May-June 2025. The population in this study were all Tb patients, both suspected and confirmed pulmonary Tb in the work area of the Tanjung Baru Health Center in 2024, totaling 67 people. The research sample that has met the inclusion and exclusion criteria was obtained as many as 45 respondents. The results showed that several independent variables such as family income, family support, knowledge and attitude of respondents were significantly associated with medication compliance (Pv<0.05). Other variables such as respondents' age, gender, education level, employment status and duration of taking medication were not associated with adherence to taking medication (Pv>0.05). Suggestions to improve efforts to manage Pulmonary TB disease by optimizing health promotion activities by cadres and health workers regarding Pulmonary TB disease and its treatment. Remind patients about the importance of taking medicine regularly and regularly according to recommendations. Remind patients that compliance in taking Lung TB drugs can minimize the risk of complications and drug resistance and increased transmission of Lung TB disease.